Conformational Studies of Oxytocin, Lysine Vasopressin, Arginine Vasopressin, and Arginine Vasotocin by Carbon-13 Nuclear Magnetic Resonance Spectroscopy - Walter, Roderich (1973)
Oxytocin, arginine vasopressin, lysine vasopressin, arginine vasotocin, as well as their cyclic and acyclic analogs, were studied by carbon-13 nuclear magnetic resonance spectroscopy in deuterium oxide and deuterated dimethylsulfoxide. Fourier-transformed spectra were obtained at 25.16 MHz. The resonances of all carbon atoms have been assigned in both solvent systems; this includes tentative assignments of the carbonyl carbons. The spectra of arginine vasopressin and lysine vasopressin are essentially identical when compared in D(2)O or dimethylsulfoxide, but they differ from those of oxytocin. The spectrum of arginine vasotocin in D(2)O is intermediate between those of oxytocin and the vasopressins. These spectral differences are not only due to variations in constituent amino acids but are also a reflection of conformational differences of oxytocin, arginine vasotocin, and the vasopressins. All hormones are sensitive to changes in hydrogen ion concentration in both solvents; this was not observed with deamino analogs, which lack the terminal amino group.